Temporal Creation and Cosmological Arguments in Early-Modern Calvinism - Sasser, Nathan (Reformation & Renaissance review, 2019)
This study examines the varieties of cosmological arguments deployed in the natural theologies of early-modern Calvinism. Some of the first Reformed forays into theistic proofs make use of Thomist arguments which allow for the logical possibility of creation from eternity. In the seventeenth century, many Reformed theologians prefer to use arguments against the possibility of an eternal world - arguments which had been defended by medieval theologians such as Bonaventure. But these arguments in turn faced criticism in the seventeenth century, and many of the Reformed supplemented them or replaced them with others. The argument from the mutability of the world to its temporal beginning became increasingly popular among Reformed thinkers. Historical arguments from the recent rise of arts and sciences or biological species supplemented the philosophical arguments for the world's beginning. Their theological commitment to the impossibility of eternal creation may explain why the Reformed did not typically use the Clarke and Leibniz argument from contingency.